Multilevel inverter with MPWM-LFT switching strategy for voltage THD minimization - M. H. Yatim; A. Ponniran; A. N. Kasiran (Institute of Advanced Engineering and Science, 2019)
This paper presents a proposed modified pulse width modulation – low frequency triangular (MPWM-LFT) switching strategy for minimization of voltage THD with implementation of asymmetric multilevel inverter (AMLI) topology on the reduced number of switching devices (RNSD) circuit structure. Principally, MPWM-LFT able to produce optimum angle of the output voltage level in order to minimize total harmonic distortion (THD). In this study, 5-level reduced number of switching devices circuit structure is selected as a circuit configuration for asymmetric (7-level structure) multilevel inverter. For switching strategy, MPWM used low switching frequency in producing signal and needs higher output voltage levels to achieve low total harmonic distortion. In contrast, sinusoidal pulse width modulation used high switching frequency in order to minimize total harmonic distortion. By optimizing angle at the output voltage using MPWM-LFT switching strategy, the voltage THD is lower as compared to MPWM and SPWM switching strategies. MPWM-LFT switching strategy obtains 11.6% of voltage THD for the 7-level asymmetric topology as compared to MPWM and SPWM switching strategies with the voltage THD are 21.5% and 17.5% respectively from the experimental works.